Relationship Between Self-Esteem and Family Social Interaction with Mental Disorders in Medan Sunggal, Medan - Nasution, Sakinah Al Muniroh; Daulay, Wardiyah (Talenta Publisher, 2020)
Family member with mental illness causes inferiority, shamefulness, and minimal function in the community.Â In some cases, mentally ill patients withdrawn from interaction and refuse to communicate.Â The objective of the research was to analyze the correlation between self-esteem and social interaction in the family with mentally ill patients in Kelurahan Medan Sunggal, Medan. This was a descriptive quantitative study with correlation method. The samples were 18 family members who suffered from a mental disorder, with purposive sampling technique. The data collection using questionnaires and data analyses is undergone with univariate analysis and frequency distribution.Â The bivariate analysis applied Spearman's Rho test. The result of the research showed that 15 respondents (83.3%) had high self-esteem and 11 respondents (61.1%) had a good social interaction. There was a significant correlation between self-esteem and social interaction in a family with a mentally ill patient (P-value = 0.012) with positive direction (r = 0.576). It is concluded that a high self-esteem correlates well with the social interaction among the family members with mental illness. It is recommended for family members to maintain their self-esteem and social interaction capacity. A mentally disorder person should get social support from family, health care providers, the government, and society.